When the expression is divided by x+2, we have:
ax^3 + bx^2 - cx + 4 = q(x)(x+2) - 22
Where q(x) is the quotient. When the expression is divided by x-1, we have:
ax^3 + bx^2 - cx + 4 = p(x)(x-1) + 2
Where p(x) is the quotient. And when the expression is divided by x-2, we have:
ax^3 + bx^2 - cx + 4 = r(x)(x-2) + 6
Where r(x) is the quotient.
We can see that the remainder when divided by x+2 is -22, so q(-2) = -22. We can also see that the remainder when divided by x-1 is 2, so p(1) = 2. And finally, the remainder when divided by x-2 is 6, so r(2) = 6.
To find a, b, and c, we need to solve these equations.
q(-2) = -22
p(1) = 2
r(2) = 6
Expanding these equations, we get:
-8a + 4b -2c + 4 = -22
a + b - c + 4 = 2
4a + 2b - 4c + 4 = 6
Simplifying these equations, we get:
-8a + 4b -2c = -26
a + b - c = -2
4a + 2b - 4c = 2
Now, we can solve these equations using any method of solving a system of equations, such as substitution or elimination. For simplicity, we will use elimination method.
Multiplying the second equation by 4, we get:
4a + 4b - 4c = -8
4a + 2b - 4c = 2
Subtracting the second equation from the first equation, we get:
2b = -10
b = -5
Substituting b = -5 into the second equation, we get:
a + (-5) - c = -2
a - c = 3
Substituting b = -5 into the third equation, we get:
4a + 2(-5) - 4c = 2
4a - 10 - 4c = 2
4a - 4c = 12
Subtracting the second equation from the third equation, we get:
4c = -9
c = -9/4
Substituting c = -9/4 into the second equation, we get:
a - (-9/4) = 3
a + 9/4 = 3
a = 3 - 9/4
a = 3/4
So, a = 3/4, b = -5, and c = -9/4.
When dividedby x+2, the expression ax^3+bx^2-cx+4 leaves remainder -22 when divided by x-1, the same expression leaves remainder 2. Given that when the expression is divided by x-2, the remainder is 6. Find a, b, c.
1 answer